Analysis of Shoreline Change Using Empirical Methods at Palik Beach, North Bengkulu - Putra, Ihza Gian Fires; Santosa , Budi (Jurnal Teknik Sipil, 2023)
Palik Beach, which is located in Lubuk Jaya Village, North Bengkulu, is a beach that is right next to each other and faces directly into the Indian Ocean, this causes this beach to have quite large waves. Large coastal waves trigger sediment transport which can cause abrasion, accretion, and shoreline changes which can disrupt fishermen’s activities in sailing to catch fish and fish auction activities in the area. This research was conducted to determine the magnitude of abrasion, accretion and shoreline changes at Palik Beach using empirical methods with numerical analysis. The empirical methods used are the Manohar Method, the Komar Method, and the CERC (SMB) Method. The results of the analysis using the Manohar Method, the largest abrasion occurred at pias 4 which was 2.47 m, the largest accretion occurred at pias 1 which was 8.91 m, the largest shoreline change occurred at pias 1 which was 8.91 m. The results of the analysis using the Komar method, the largest abrasion occurred at pias 4, namely 1.84 m, the largest accretion occurred at pias 1, namely 7.85 m, the largest shoreline change occurred at pias 1, namely 7.85 m. The results of the analysis using the CERC method, the largest abrasion occurred at pias 4 which was 1.51 m, the largest accretion occurred at pias 1 which was 6.44 m, the largest shoreline change occurred at pias 1 of 6.44 m